2016
DOI: 10.1002/pc.23988
|View full text |Cite
|
Sign up to set email alerts
|

Powder binders used for the manufacturing of wind turbine rotor blades. Part 1. Characterization of resin‐binder interaction and preform properties

Abstract: Glass fiber reinforced plastics (GFRP) are the predominant materials used for wind turbine rotor blades. To manufacture blades in a vacuum-assisted resin infusion process (VARI), a binder is needed for fiber fixation and preform stability. Moreover, solubility and mechanical compatibility of the binder and the epoxy resin matrix are important parameters for processability and the mechanical properties of the composite. The present study therefore characterized and evaluated five chemically different binders wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…In the aviation and renewable energy sectors, epoxy resins are widely employed in fiber reinforced composites for the manufacture of structural parts of airplanes and wind turbines. [1][2][3][4][5][6] Epoxy resins are, to a large extent, utilized in more conventional applications such as engineering adhesives, coatings and paints as well as matrix for fabrication of electronic parts in consideration of the resins' excellent adhesion strength and processability. Since its discovery, the use of epoxy resins had become prevalent in composite research and development.…”
Section: Introductionmentioning
confidence: 99%
“…In the aviation and renewable energy sectors, epoxy resins are widely employed in fiber reinforced composites for the manufacture of structural parts of airplanes and wind turbines. [1][2][3][4][5][6] Epoxy resins are, to a large extent, utilized in more conventional applications such as engineering adhesives, coatings and paints as well as matrix for fabrication of electronic parts in consideration of the resins' excellent adhesion strength and processability. Since its discovery, the use of epoxy resins had become prevalent in composite research and development.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, they focused on the influence of preforming conditions to adjust resin flow behavior. Schmidt et al [51] concentrated on the solubility of epoxy binders after infusing and curing of composite glass fiber plates. The influence on the mechanical behavior was characterized and concluded that interface formations due to partial solubility decrease interlaminar bonding.…”
Section: Flow In the Presence Of Bindermentioning
confidence: 99%
“…When impregnating a Bindered Preform during an LCM process, binder dissolution is an expected phenomenon. The resulting solution deviates in terms of chemo-rheological properties and is still considered a major unknown factor [26,50,51]. The powder binder and the test liquid RIMR135 are both based on bisphenol-A and mainly differ in terms of their molecular length; hence, the binder is frozen at room temperature, while the resin is still in liquid form.…”
Section: Binder Dissolutionmentioning
confidence: 99%
“…In relation to fibre-reinforced composite materials, polymer powders have also been investigated as binders which help to bond individual plies of fabric together and produce a preform for subsequent resin infusion [20,31,32]. For these studies, the main topics of interest were the solubility of the binder in the infusion resin and the effect of binders on both the processing parameters and the mechanical properties of composite materials.…”
Section: Resin System Typementioning
confidence: 99%